Study on the effect of chrysanthemum polysaccharide on hypoglycemic in type 2 diabetic rats - ZHAO Kai-di; WANG Qiu-dan; LIN Chang-qing (Shipin yu jixie, 2022)
Objective: This study aimed to investigate the hypoglycemic effect of chrysanthemum polysaccharide on type 2 diabetes (T2DM) rats. Methods: The chrysanthemum polysaccharides were extracted by water extraction and alcohol precipitation. After feeding rats with high-fat and high-sugar feed for 6 weeks, STZ (30 mg/kg·BW) was injected intraperitoneally to establish a T2DM rat model, and records were recorded during the experiment. Rat body weight, food intake, water consumption, fasting blood glucose (FBG) was measured every two weeks, and glucose tolerance (OGTT) test was performed in the last week of the test; the insulin (INS) level was measured by Elisa method, and insulin resistance was calculated Index (HOMA-IR). Determination of total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C) levels, as well as the levels of superoxide dismutase (SOD), cystathione (GSH), catalase (CAT), and malondialdehyde (MDA) were detected by Western Blot to detect the expression levels of Nrf2, Keap1, and HO-1. Results: Treatment with chrysanthemum polysaccharides could alleviate the weight loss of T2DM rats, reduce their food intake and water consumption, improve the glucose tolerance of T2DM rats, and reduce INS and HOMA-IR in rats. It could significantly reduce the levels of TC, TG, LDL-C in T2DM rats (P＜0.05), and significantly increase the level of HDL-C (P＜0.05). The levels of SOD, GSH and CAT in T2DM rats increased significantly (P＜0.05), and the level of MDA decreased significantly (P＜0.05). The Nrf2, Keap1, and HO-1 protein levels of T2DM rats treated with chrysanthemum polysaccharides tended to normal protein levels. Conclusion: Chrysanthemum polysaccharide can effectively improve the symptoms of "three more and one less" in T2DM rats, reduce FBG levels, increase OGTT, improve INS levels and HOMA-IR, improve abnormal lipid metabolism and oxidative stress levels in T2DM rats, and through regulation Nrf2/Keap1/HO-1 pathway related proteins play a role in the treatment of T2DM.